The metacognitive reading strategy awareness of first year EFL BA students: A mixed-methods study - Szűcs, Ágota (Working Papers in Language Pedagogy, 2017)
Reading comprehension skills are a crucial set of skills which university students need. Even though these skills are not under-researched in either the international or the Hungarian context, research on the reading strategy awareness of first-year BA students at the beginning of their university studies is not extensive. In Hungary, no recent comprehensive studies investigating the input students receive in high school regarding reading strategy training can be found. Therefore, the aim of the present project is to explore the reading strategy awareness of first-year English major BA students, the reading skills training they received at high school, and to compare and contrast that training with the requirements stipulated in the official high school curriculum. To complete this research endeavour, a mixed-methods study was designed, involving a questionnaire and an interview study. The findings indicate that first-year university students lack the necessary reading strategies, and therefore the data suggests that offering targeted training to improve reading comprehension skills should be made part of not only secondary but also tertiary education. Raising students’ reading strategy use awareness is important because during their university studies they are constantly faced with tasks requiring excellent reading skills.